2006
DOI: 10.1128/iai.01104-06
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Forms of Adenylate Cyclase Toxin ofBordetella pertussison Protection Afforded by an Acellular Pertussis Vaccine in a Murine Model

Abstract: Four recombinant forms of the cell-invasive adenylate cyclase toxin (CyaA) of Bordetella pertussis were compared for the ability to enhance protection against B. pertussis in mice when coadministered with an acellular pertussis vaccine (ACV). The four forms were as follows: fully functional CyaA, a CyaA form lacking adenylate cyclase enzymatic activity (CyaA*), and the nonacylated forms of these toxins, i.e., proCyaA and proCyaA*, respectively. None of these forms alone conferred significant (P > 0.05) protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
45
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 58 publications
2
45
1
2
Order By: Relevance
“…This is similar to the sticky behavior observed when ACT without urea was applied to and retained by the SEC column and likely reflects the presence of solventexposed hydrophobic patches in misfolded ACT molecules. Monomeric RTX 985 did not bind the ␣ M ␤ 2 receptor, consistent with prior studies showing that post-translational acylation is essential for receptor binding (29,54). In summary, the individual domains were readily purified, with yields of CAT 400 at ϳ80 mg/liter culture, nonacylated RTX and HP domains at ϳ5 mg/liter culture, and the acylated domains at Ͻ2 mg/liter culture.…”
Section: Volume 290 • Number 6 • February 6 2015supporting
confidence: 70%
See 1 more Smart Citation
“…This is similar to the sticky behavior observed when ACT without urea was applied to and retained by the SEC column and likely reflects the presence of solventexposed hydrophobic patches in misfolded ACT molecules. Monomeric RTX 985 did not bind the ␣ M ␤ 2 receptor, consistent with prior studies showing that post-translational acylation is essential for receptor binding (29,54). In summary, the individual domains were readily purified, with yields of CAT 400 at ϳ80 mg/liter culture, nonacylated RTX and HP domains at ϳ5 mg/liter culture, and the acylated domains at Ͻ2 mg/liter culture.…”
Section: Volume 290 • Number 6 • February 6 2015supporting
confidence: 70%
“…As a result, passively administered antibodies blocking ACT function may be able to enhance neutrophil-mediated phagocytosis of opsonized bacteria (67). Murine studies have shown that immunization with ACT alone or as a supplement to the acellular vaccine reduces bacterial colonization, an effect that correlated with increased immunoglobulin levels and a Th1/Th2 cytokine phenotype (16,54). Finally, ACT is a highly conserved antigen, able to induce protective immunity in mouse models against the three dominant Bordetella species (B. pertussis, B. parapertussis, and B. bronchiseptica) (70 -72).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the impact an adolescent booster would have on infant pertussis is yet to be determined. However, further development of acellular pertussis vaccines, e.g., with additional antigens (47,48) or adjuvants (49,50), could lead to better efficacy of the adolescent booster and thus induction of sustainable protection into the childbearing years. Studies have shown that whole-cell pertussis vaccines seem to offer better protection than acellular vaccines (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…Addition of new antigens to the vaccine has been suggested as a solution to this resurgence (2). A leading candidate for inclusion in future acellular vaccine formulations is the adenylate cyclase toxin (ACT) because it is essential for virulence, immunogenic, and a demonstrated protective antigen (3)(4)(5)(6). ACT is composed of a 400-amino-acid C-terminal catalytic domain and a 1,306-amino-acid cell-binding domain that is homologous to the repeats in toxins (RTX) family of pore-forming bacterial protein toxins (7).…”
mentioning
confidence: 99%